2018
DOI: 10.2147/nss.s155733
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate phenotypes and clinical correlates in a large cohort of adults without sleep apnea

Abstract: BackgroundNormal sleep is associated with typical physiological changes in both the central and autonomic nervous systems. In particular, nocturnal blood pressure dipping has emerged as a strong marker of normal sleep physiology, whereas the absence of dipping or reverse dipping has been associated with cardiovascular risk. However, nocturnal blood pressure is not measured commonly in clinical practice. Heart rate (HR) dipping in sleep may be a similar important marker and is measured routinely in at-home and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 103 publications
(102 reference statements)
0
7
0
1
Order By: Relevance
“…They found white women have decreased parasympathetic tone and elevated sympathetic tone during NREM stage 2 and REM sleep compared to their African American and Chinese counterparts after controlling for confounding factors such as recording length and respiratory rate (205). Huang et al (206) have shown heart rate profiles in a larger cohort of adults without sleep apnea in order to develop heart rate phenotypes regarding sleep physiology. They implied that heart rate dipping and spectral HRV metrics could contribute to sleep phenotyping due to their significant correlations to sleep measures (e.g., sleep stage, total sleep time and sleep quality).…”
Section: Effect Of Age Ethnicity and Sex On Hrvmentioning
confidence: 99%
“…They found white women have decreased parasympathetic tone and elevated sympathetic tone during NREM stage 2 and REM sleep compared to their African American and Chinese counterparts after controlling for confounding factors such as recording length and respiratory rate (205). Huang et al (206) have shown heart rate profiles in a larger cohort of adults without sleep apnea in order to develop heart rate phenotypes regarding sleep physiology. They implied that heart rate dipping and spectral HRV metrics could contribute to sleep phenotyping due to their significant correlations to sleep measures (e.g., sleep stage, total sleep time and sleep quality).…”
Section: Effect Of Age Ethnicity and Sex On Hrvmentioning
confidence: 99%
“…As shown in Figure 2, the ISSD phenotype has also been associated with specific adverse health outcomes in 37 studies: Cardiovascular (Bathgate et al, 2016; Bertisch et al, 2018; Fernandez‐Mendoza et al, 2012; Fernandez‐Mendoza et al, 2018; Hein et al, 2019a; Hein et al, 2019b; Huang et al, 2018; Nakazaki et al, 2012; Sigurdardottir et al, 2022; Vgontzas et al, 2009a). Metabolic (Castro‐Diehl et al, 2018; D'Aurea et al, 2015; Duan et al, 2023; Hein et al, 2018; Miner et al, 2022; Vasisht et al, 2013; Vgontzas et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…The ISSD phenotype, defined in adults as self‐reporting insomnia disorder and sleeping objectively for <6 h (Vgontzas et al, 2013), has been characterised by 24‐h physiological hyperarousal in 21 studies as measured by: Increased alertness/decreased physiological sleep propensity (Bonnet & Arand, 1995; Bonnet & Arand, 1998b; Dorsey & Bootzin, 1997; Sugerman et al, 1985). Sympathetic/parasympathetic imbalance (Bonnet et al, 2014; Bonnet & Arand, 1995; Bonnet & Arand, 1998a; Huang et al, 2018; Jarrin et al, 2018b; Miller et al, 2016; Spiegelhalder et al, 2011). Stress system (HPA and SAM axes) activation (Castro‐Diehl et al, 2015; Castro‐Diehl et al, 2016; D'Aurea et al, 2015; Vgontzas et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations